Dietary hydrolysed yeast cell wall extract is comparable to antibiotics in the control of subclinical necrotic enteritis in broiler chickens. Issue 6 (2nd November 2019) - Ahiwe, E. U.; Chang'a, E. P.; Abdallh, M. E.; Al-Qahtani, M.; Kheravii, S. K.; Wu, S.; Graham, H.; Iji, P. A.
ABSTRACT: 1. The aim of this study was to examine the effect of yeast cell wall (YCW) on performance and physiological responses of broiler chickens under subclinical necrotic enteritis challenge. 2. Six treatments in a 2 × 3 factorial arrangement (non-challenged or challenged plus no supplement, YCW or antibiotics (AB)) was used. Each treatment was replicated eight times with 12 birds per replicate. The treatments included: (1) Positive control (PC; no additive, not challenged); (2) Negative control (NC; no additive, with challenge); (3) YCWN = yeast cell wall (2.0 g/kg diet, not challenged; (4) YCWC = yeast cell wall (2.0 g/kg diet, challenged); (5) ABN = zinc bacitracin 50 ppm + Salinomycin 60 ppm, not challenged); (6) ABC = zinc bacitracin 50 ppm + Salinomycin 60 ppm, challenged). 3. Eimeria challenge at 9 d of age did not affect feed intake (FI), body weight gain (BWG), FCR or liveability at 10 d. The BWG and FCR at 10 d were greater (P < 0.05) in birds fed YCW or AB (AB) diets relative to the PC or NC groups. On 24 and 35 d, FI, BWG, FCR and flock uniformity (28 d) were greater (P < 0.05) in the challenged groups fed YCW or AB diets compared to NC group. 4. Supplementation with YCW ameliorated the negative effects of NE on liver, spleen and bursa weight of birds. 5. Necrotic enteritis challenge decreased (P < 0.05) caecal Lactobacillus and Bifidobacterium spp . counts, and increased ileum lesion score and caecal Clostridium perfirngens counts. This was reversed by the addition of either YCW or AB. 6. Supplementation with YCW and AB resulted to a greater (P < 0.05) dressing percentage and meat yield (35 d). 7. The results indicated that YCW plays a vital role in improving the physiological response and performance of broiler chickens under subclinical necrotic enteritis challenge.